Building confidence : electronic commerce and development (UN New YorkUS)
Looks at e-commerce and development; focal and legal aspects of e-commerce; electronic commerce in transport services; and, e-commerce and financial services. Focuses on the state of e-commerce and presents an agenda for action.
Keywords: BUSINESS